2015
DOI: 10.5539/ass.v11n11p308
|View full text |Cite
|
Sign up to set email alerts
|

Management Aspects of Production Cost Accounting in Horse Breeding

Abstract: The particular management accounting lines are considered in the present paper, based on the state and current practice of production cost accounting study and calculation of production cost of horse breeding in the analyzed companies, to help the enterprise management in making reasonable decisions regarding maintenance of cost management in the given industry. The criteria of breakeven point, marginal income, and safety edge can be used for production planning, decision-making on pricing for prediction of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…Klychova et al (2015) also explained that: "the purpose of this method is increasing the speed of decisionmaking on pricing and possibility of analyzing the relationship of the costs, volume of production (sales) of products and profit (CVP-analysis) as well as analysis of break-even point" (p. 308). Additionally, Iotti and Bonazzi (2014) explained that "the direct costing assigns only the costs directly attributable to the individual productions, while overhead costs are not allocated and are briefly summarized at the close of the reclassified income statement" (p. 1492).…”
Section: Financial Criteria For Evaluating the Innovation Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Klychova et al (2015) also explained that: "the purpose of this method is increasing the speed of decisionmaking on pricing and possibility of analyzing the relationship of the costs, volume of production (sales) of products and profit (CVP-analysis) as well as analysis of break-even point" (p. 308). Additionally, Iotti and Bonazzi (2014) explained that "the direct costing assigns only the costs directly attributable to the individual productions, while overhead costs are not allocated and are briefly summarized at the close of the reclassified income statement" (p. 1492).…”
Section: Financial Criteria For Evaluating the Innovation Managementmentioning
confidence: 99%
“…About the direct costing, Klychova, Zakirova, Zakirov, and Valieva (2015) indicated that "is intended to include in the cost of production and ending stocks estimate only variable production costs and allocation on financial result of the total amount of fixed costs without distribution by product types" (p. 308). Klychova et al (2015) also explained that: "the purpose of this method is increasing the speed of decisionmaking on pricing and possibility of analyzing the relationship of the costs, volume of production (sales) of products and profit (CVP-analysis) as well as analysis of break-even point" (p. 308).…”
Section: Financial Criteria For Evaluating the Innovation Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Klychova et al (2015) also explained that: "the purpose of this method is increasing the speed of decision-making on pricing and possibility of analyzing the relationship of the costs, volume of production (sales) of products and profit (CVPanalysis) as well as analysis of break-even point" (p. 308). Additionally, Iotti and Bonazzi (2014) explained that "the direct costing assigns only the costs directly attributable to the individual productions, while overhead costs are not allocated and are briefly summarized at the close of the reclassified income statement" (p. 1492).…”
Section: Financial Criteria For Evaluating the Innovation Managementmentioning
confidence: 99%
“…About the direct costing, Klychova, Zakirova, Zakirov, and Valieva (2015) indicated that "is intended to include in the cost of production and ending stocks estimate only variable production costs and allocation on financial result of the total amount of fixed costs without distribution by product types" (p. 308). Klychova et al (2015) also explained that: "the purpose of this method is increasing the speed of decision-making on pricing and possibility of analyzing the relationship of the costs, volume of production (sales) of products and profit (CVPanalysis) as well as analysis of break-even point" (p. 308).…”
Section: Financial Criteria For Evaluating the Innovation Managementmentioning
confidence: 99%